Babesia bovis infection in cattle in the southwestern Brazilian Amazon - Brito, Luciana G.; Rocha, Rodrigo B.; Barbieri, Fábio da S.; Ribeiro, Elisana S.; Vendrami, Fabiano B.; Souza, Gislaine C.R.; Giglioti, Rodrigo [UNESP]; Regitano, Luciana C.A.; Falcoski, Thaís O.R.S. [UNESP]; Tizioto, Polyana C.; Oliveira, Márcia C.S. (Elsevier, 2013)
The present study provides the first epidemiological data on infection with Babesia bovis in cattle raised in the southwestern Brazilian Amazon. Blood clot samples were filtered through nylon cloth before being submitted to DNA extraction. PCR and nested-PCR were applied to assess the frequency of infection with B. bovis in calves with ages from 4 to 12 months bred in 4 microregions each in the states of Rondônia and Acre. After the DNA was extracted from the samples, the infection in cattle was investigated by amplification of the rap1 gene from B. bovis. The DNA amplification results revealed a frequency of infection with B. bovis of 95.1% (272/286) in the samples from Rondônia and 96.1% (195/203) in those from Acre. The high frequency of B. bovis infection in the animals with ages from 4 to 12 months indicates a situation of enzootic stability in the regions studied. The infection rates are comparable to those detected by immunodiagnostic techniques in other endemic regions of Brazil. © 2012 Elsevier GmbH.
Keywords: Amazonia; Babesia bovis; Brazil; Cattle; Epidemiology; Rap1 protein; blood clot; blood sampling; calf (bovine); cattle; controlled study; DNA extraction; DNA isolation; gene; gene amplification; infection rate; nested polymerase chain reaction; nonhuman; nucleotide sequence; piroplasmosis; polymerase chain reaction; priority journal; rap1 gene; sensitivity and specificity; serodiagnosis; Animals; Babesiosis; Cattle Diseases; DNA, Protozoan; Polymerase Chain Reaction; Sensitivity and Specificity; Animalia; Bos